Baby hamster kidney cell–derived recombinant factor VIII: a quarter century of learning and clinical experience. Issue 12 (1st December 2016) - Afonja, Olubunmi; Kozak, Robert; Petraro, Paul; Michaels, Lisa A.; Mathew, Prasad; Lemm, Georg; Kessler, Craig
ABSTRACT: Introduction : Management and care of individuals with hemophilia A advanced immensely with the introduction of recombinant factor VIII (rFVIII) replacement products. This review provides a historical overview of rFVIII development with a focus on Bayer's rFVIII (with albumin) and sucrose-formulated rFVIII (rFVIII-FS), the only rFVIII products cloned in baby hamster kidney (BHK) cells with >25 years of proven safety and efficacy. Areas covered : We review the advances in rFVIII technology and the efficacy and safety data for BHK-derived rFVIII/rFVIII-FS from clinical trials, investigator-initiated studies, and observational studies. Innovative products with new treatment potentials (eg, BAY 81-8973 and BAY 94-9027) built on this established safety and efficacy profile are also briefly discussed. The literature search strategy included targeted searches (PubMed) with manual article selection and other product-specific searches. Expert commentary : Development of rFVIII products and related improvements in viral safety and manufacturing efficiency have guaranteed an adequate supply of factor products worldwide and increased prophylaxis use. The net effects have been joint health preservation, reduction in morbidity and mortality, and quality-of-life enhancements. Current treatment challenges include lack of adherence to prophylaxis and inhibitor development; extended-half–life rFVIII products and non-FVIII replacement therapies in development may help overcome these challenges.